An Analysis of Factors Influencing Investment Decisions Among Generation Z in the Capital Market: A Case Study of Surabaya - Irvinta, Irvinta Mestika Sari; Yuniningsih, Yuniningsih; Tika , Tri Kartika Pertiwi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study looks at the impact of locus of control, risk tolerance, and social media influencers on investing decisions among Generation Z in Surabaya, with financial literacy serving as a moderator. Indonesia has seen a considerable increase in young investors; however, their general lack of financial literacy may have an impact on the quality of their investment choices. The study used a quantitative research approach and questioned 150 Gen Z respondents who are active capital market investors and often interact with financial information on social media. Using SmartPLS 4.0 to analyze data, the findings show that locus of control and risk tolerance have a considerable positive effect on investment decisions. In contrast, there is no statistically significant direct effect from social media influencers. Furthermore, the study discovered that financial literacy considerably modifies the relationship between locus of control and investing decisions. It does not, however, appreciably mitigate the effects of risk tolerance or social media impact. These findings are consistent with Decision Affect Theory, which emphasizes the relevance of individual emotions and perceived control in financial decision-making. To provide a more complete picture, future study should expand the sample size and investigate additional variables such as investment experience and economic situations. Overall, this study provides useful information for improving financial literacy and implementing effective investing strategies for Generation Z in the digital era.